THE INFLUENCE OF LEADERSHIP STYLE AND WORK ENVIRONMENT ON EMPLOYEE JOB SATISFACTION IN THE SUPPLY DEPARTMENT OF PT. INDOCEMENT TUNGGAL PRAKARSA Tbk CIREBON: LEADERSHIP STYLE, WORK ENVIRONMENT, JOB SATISFACTION - Pratiwi, Vina Andita; Bahtiar, Rizki Akbar; Suwandi, Suwandi; Trimayanti, Imas (Indonesia Auditing Research Journal, 2024)
Influence of Leadership Style and Working Environment towards Job Satisfaction at Supply Department PT Indocement Tunggal Prakarsa Tbk Cirebon The purpose of the research are: 1) To know description for leadership style, Working Environtment, and job satisfaction at Supply Department PT Indocement Tunggal Prakarsa Tbk Cirebon. 2) Test empirically influence of leadership style towards job satisfaction at Supply Department PT Indocement Tunggal Prakarsa Tbk Cirebon. 3) Test empirically influence of working environment towards job satisfaction at Supply Department PT Indocement Tunggal Prakarsa Tbk Cirebon 4) Test empirically influence of leadership style and Working Environment towards at Supply Department PT Indocement Tunggal Prakarsa Tbk Cirebon. The analysis implemented in this research are simple regression and multiple regression analysis. The method of this research is simple random sampling, that taken 67 employees at Personal General Affairs Division, Finance Division, Distribution Division and Logistic Division , while data collecting by using quitionaire and cultivated using SPSS 25.0. The result of t test for leadership style is 3.286, and the signification is 0.002. This shows that there is an effect between leadership style towards job satisfaction. The result of t test for Working Environtment is 2.237, and the signification is 0.029. This shows that there is an effect between organization culture towards job satisfaction. The result of F test is 13.806, and the signification is 0.000. This shows that there is an effect between leadership style and organization culture towards job satisfaction. The result of R2 is 0.301 or 30.1%. It means Job Satisfaction is affected by leadership style and working environtment as much as 30.1%.